Recruiting and Preparing skilled personnel for leadership roles in welding and brazing - Cole, N.; Weber, J.; Pfarr, M.; Hernandez, D. (Автоматическая сварка, 2013)
A shortage of welders and welding professionals is felt globally, and it will worsen as the current skilled and educated leave the workforce. Thus, many countries are actively designing programs to improve the image of welding and to train and educate persons to meet those needs. Virtual welding, by means of computer simulation, is one method of introducing and exciting the young about welding. Some companies are even using the virtual welder as to test or even give basic training to new employees. Females are 50% of the population, yet too few choose welding. We have good role models in the many different areas of welding and they are highlighted here. Once persons are interested in welding, they need to be properly trained and educated. Weld-Ed is a program in the USA that has 1) a model curriculum for 2-year colleges; 2) a program to update and upgrade instructors; 3) a method of pairing industry with schools and colleges to offer necessary skills and knowledge for available jobs. New technology is being used by several countries in a variety of ways to enhance training and education. Several types, including online learning and electronic devices, will be described. As persons become skilled and educated, they need a way to prove their competence. A cost-effective means of demonstrating their competence is a Certification Program. Bright young persons are needed in welding science and technology to meet national and global challenges. Our future, structures, and infrastructure depend on them.